COMPARISON OF THERAPISTS’ AND FAMILY DOCTORS’ CONCEPTIONS CONCERNING DIAGNOSTICS AND TREATMENT OF ACUTE BRONCHITIS - Bereznyakov, I.G.; Imanova, N.I.; Bereznyakov, V.I.; Lebedynska, M.N.; Levadna, I.V.; Shepitko, K.V. (World of Medicine and Biology, 2019)
Physicians’ mistakes in diagnostics and treatment of acute bronchitis (AB) lead to unnecessary drug costs and can negatively influence on spread of antimicrobial resistance. The purpose of the study was to identify and explain common misconceptions regarding the diagnosis and treatment of patients with AB by interviewing internists and family physicians of Ukraine and Kazakhstan. There were 8 questions formulated to physician’s inquiry with 5 variants of responses to each of them. Surveys were carried out from December 2017 to November 2018 at medical conferences and courses of postgraduate education for physicians. Among the common physicians’ misconceptions in both countries we can highlight 1) the widespread use of aminopenicillins (including ones with β-lactamase inhibitors), which are not active against main pathogens of АB, 2) predominant appointment of mucolytics and / or mucokinetics, and expectorants, with quite modest evidence of their effectiveness in AB, 3) preference herbal medicines with limited proven effectiveness.
Keywords: acute bronchitis; inquiry; internists; family physicians; Ukraine; Kazakhstan